Evaluasi Buku Interaktif Berbasis Augmented Reality Menggunakan System Usability Scale dan User Experience Questionnaire - Dinan Yulianto; Rudy Hartanto; Paulus Insap Santosa (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Nowadays, the implementation of information and communication technology in education is important. In harmony with technological developments, the term mobile learning comes to represent learning that utilizes mobile communication devices. The implementation of augmented reality in education provides a new learning model in the form of a combination of technology-based conventional learning media. This research aimed to evaluate augmented reality-based books as media for learning Cirebon mask dance. As many as 15 respondents were involved in the evaluation process, including testing the usability using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). The evaluation using SUS found a value of 77.67, meaning that the Acceptability Ranges category was “Acceptable”; the Grade Scale category was “C”; and the Adjective Rating category was “Excellent”, while that using UEQ found that each category, namely Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, Dependability, and Novelty got a value greater than the impression value (0.8), namely 2.122; 2.117; 1.983; 1.750; 1.950 and 1,867, respectively. Overall, all of the evaluation results show that augmented reality-based books are acceptable to be used as media for learning Cirebon mask dance.